2021
DOI: 10.2196/29694
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity to UV Radiation Exposure Monitoring Using Personal Exposure Devices for Skin Cancer Prevention: Longitudinal Observational Study

Abstract: Background Emerging UV radiation (UVR) monitoring devices may present an opportunity to integrate such technology into skin cancer prevention interventions. However, little is known about the effects of using a wearable UVR monitor on adults’ and children’s sun protection–related behaviors and attitudes (eg, cancer worry and perceived risk). Understanding the potential role of reactivity and seasonal effects will help inform the use of objective monitors in the context of skin cancer prevention res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The most dominant study design was observational (n=28, 60.9%) [ 17 , 20 , 21 , 23 - 25 , 27 , 28 , 31 , 32 , 34 , 36 - 40 , 42 - 47 , 49 - 51 , 57 , 58 , 60 ], followed by randomized trials (n=10, 21.7%) [ 19 , 22 , 26 , 30 , 35 , 41 , 52 - 55 ], post hoc analyses of RCTs (n=5, 10.9%) [ 18 , 29 , 56 , 59 , 61 ], and post hoc analyses of observational studies (n=3, 6.5%) [ 16 , 33 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most dominant study design was observational (n=28, 60.9%) [ 17 , 20 , 21 , 23 - 25 , 27 , 28 , 31 , 32 , 34 , 36 - 40 , 42 - 47 , 49 - 51 , 57 , 58 , 60 ], followed by randomized trials (n=10, 21.7%) [ 19 , 22 , 26 , 30 , 35 , 41 , 52 - 55 ], post hoc analyses of RCTs (n=5, 10.9%) [ 18 , 29 , 56 , 59 , 61 ], and post hoc analyses of observational studies (n=3, 6.5%) [ 16 , 33 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…We chose an attention-control group over no intervention so that we could objectively measure UVR exposure in both groups and increase engagement in the control group over the 12-week intervention. A 2021 study that used the Shade device and control mobile application found that unintentional tanning and time spent outside decreased among children (aged 8-17) who wore the device for a two-week period; however, no changes in UVR exposure or sunburn were observed [29]. Notably, the study also observed that sunscreen use decreased over the study period, with the authors concluding this change could dampen the detection of intervention effects.…”
Section: Plos Onementioning
confidence: 96%
“…Another typical application is sun protection. A study on the correlation between wearing an ultraviolet (UV) monitoring device and UV exposure showed that outdoor activity time and sunscreen use time among parents and children changed significantly after wearing the monitoring device for 2 weeks [ 25 ], highlighting the potential effect of preventing skin cancer using wearable UV monitoring devices.…”
Section: Current Applications Of Digital Medicine In Oncologymentioning
confidence: 99%